Cognitive status of older adults and psychological burden on their primary caregivers (European Journal of Health Research, 2026)
Introduction: Caregivers of older adults with neurocognitive disorders present high levels of stress and health problems. Objective: Determine the relationship between the patient’s cognitive status and the burden of their primary caregiver seen in the Specialized Consultation of the CITED (National Center for the Study of Neurocognitive Disorders) between January and December 2021. Methodology: Observational, descriptive, cross-sectional study. The sample was intentionally and non-probably formed with 80 older adults who met the selection criteria and an equal number of primary caregivers. Caregiver interviews were conducted, and the Zarit Burden Scale was used, as well as the MoCA, Katz, and Lawton scales for the patients. The dependent variable was burden, and the explanatory variables selected were: patient cognitive status, age, sex, education level, relationship, time and type of care, and functionality for basic and implemented activities of daily living. Results: 51.3% of caregivers presented burden. The change in caregiver burden was influenced by the patient’s cognitive functioning status, although adjusting the regression model for other caregiver, patient, and care variables slightly reduced the effect on caregiver burden B (IC95%) of -3.550 to -1.571. Conclusion: Caregiver burden levels are high, and are associated with the cognitive functioning of older adults.
Keywords: caregivers; burden; associated factors; cognitive status